Study on the Composition of the Epiphytic Periphyton in the Gemenc Floodplain Area in Hungary - Mátrai, Ildikó; Vida-Varga, Éva; Lakatos, Gyula (Advances in Social Sciences Research Journal, 2022)
The specific aspects of wetlands are fundamentally determined by the hydrological factors and the water-related living world. In the life of wetlands the flora has its different forms of life and its connection to the water decisive roles, which are of course the results of the evolutionary processes of long periods. In this paper we give an outline about the ecological state of the macrophytes and epiphyton composition from the good state to the bad and polluted ones. It is known the degree of water supply and the water quality of the wetland determine primarily the potential vegetation and its structure. The Gemenc wetlands represent those values of the Danubian floodplains, that are the most significant, and are the mostly exposed to injuries. The aim of nature conversation is the maintenance of the now scattered remains of former wetlands, and as far as possible the reconstruction of the changed habitats. From the point of view of the EU Water Framework Directive (WFD) is it an important and significant biological index, because the data of the examination of the peripyton can be effectively used for the determination and specification of the ecological state of the Nyéki-Holt-Danube, in Gemenc floodplain (wetland). We collected plants like reed (Phragmites australis (Cav.) Trin,, great bulrush (Schoenoplectus lacustris L.), pondweed (Potamogeton lucens L.), and water-rose (Nuphar lutea (L.) Sibth) separately from the different sampling places for the epiphytic periphyton examination. The Non-Taxonomic Periphyton Index (NTPI) is the index number, that constitute of the non-taxonomic parameters of the periphyton (mass, content of ash, concentration of chlorophyll-a, AI, etc.), used relatively rapidly and professionally relevantly to evaluate the ecological state of waters. Our aim by the ecological state estimation of the Nyéki-Holt-Danube was to fix a basic state that we want to use as a reference-state under the evaluation of the effect of the further rehabilitation actions.